NATIONAL POLICY OF MODERNIZATION OF THE PUBLIC MANAGEMENT AND ROLE OF THE REPUBLIC GENERAL COMPTROLLER - Pazos Acosta, Lázaro (2017)
The research made possible to determine that the Public Management Modernization Policy (PNMGP) does not apply to the inherent activities of the Republic General Comptroller (CGR), although it is mandatory for all Public-Sector organizations- among other things-to bring the State closer to the citizens. From this objective, a descriptive analysis was performed on the relationship between the variables, and the SPSS-21 software was used for the chi-square statistical test. In this sense, the main results obtained were that there is no relationship between the PNMGP and the management model for the fight against corruption by the CGR. In this same order and direction it is shown that the Republic General Comptroller has been acting with internal regulations not updated to the PNMGP that do not yield the fruits to reduce corruption, although from 2009 to 2016 the budget for results has been increased notably, it does not manage to reduce deficiencies in the provision of public services (Health, education, transportation, housing, among others), which end up having a negative impact on the citizen’s perception of the performance of the State, since government control is ineffective in terms of impairment of the great millennium goals that seeks to end poverty, zero hunger, health and welfare, quality education, gender equality, clean water and sanitation, among others.